Quelle durabilité des formes de régulation des conflits littoraux ? - Anne Cadoret (VertigO)
The regulation of conflicts in the coastal zones constitutes a major stake for an integrated coastal zone management, however several antagonisms are controlled in the urgency or don’t find exits sufficiently relevant and reappear thereafter, sometimes in a recurring way. Our researches on conflict dynamics in coastal zones resulted in questioning us on the effectiveness and the durability of the forms of management of oppositions. Starting from many case studies, we present here a framework of reading of the factors playing an important role in the durable regulation of the oppositions, able to be useful for the observer as for the actors in charge of the management of a territory submitted to multiple antagonisms.